HUBUNGAN PENGETAHUAN DENGAN PERSEPSI KEPATUHAN HAND HYGIENE MAHASISWA PROGRAM STUDI NERS UNIVERSITAS ‘AISYIYAH YOGYAKARTA - Nur Imallah, Rosiana (MEDIA ILMU KESEHATAN, 2019)
Background: The fifth goal of patient safety establishing hand hygiene as one effective way to prevent and control Healthcare Associated Infections (HAIs). Of the efforts to support the successful implementation of hand hygiene is the obedience, knowledge and perceptions of nurse students who are practicing in hospitals. Objective: The purpose of this study was to determine the association of knowledge with the perception of hand hygiene compliance of ners students of Aisyiyah University Yogyakarta. Methods: The study design was descriptive correlational. The sample in this study were 40 nurse students of ‘Aisyiyah University Yogyakarta 2017/2018 academic year by purposive sampling technique. The instrument in this study used a questionnaire, then analyzed with Kendal Tau. Results: The association between knowledge and perception toward hand hygiene compliance was not significant (p= 0.611 (> 0.05). p value > 0.05 indicates no relationship between knowledge level and perception of hand hygiene compliance. Conclusion: There is no association between knowledge and perception of hand hygiene compliance of ners students of 'Aisyiyah University Yogyakarta. The suggestion in this study is to prepare students to behave obediently to do hand hygiene through the learning process in the classroom. Keywords: Hand hygiene, knowledge, perception, student Nurses